Resenha do livro Jango: as múltiplas faces, de Jorge Ferreira e Ângela de Castro Gomes - Rodeghero, Carla Simone (Anos 90, 2007)
Resenha do livro Jango: as múltiplas faces, de Jorge Ferreira e Ângela de Castro Gomes.